2010
DOI: 10.3109/08916930903567492
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sclerosis risk markers in HLA-DRA, HLA-C, and IFNG genes are associated with sex-specific childhood leukemia risk

Abstract: Previous epidemiologic studies showed four times increased risk of acute lymphoblastic leukemia (ALL) in children of women with multiple sclerosis (MS). MS shows a risk association with Human leukocyte antigens (HLA)-DRA single nucleotide polymorphism (SNP) rs3135388, which is a proxy marker for DRB1*1501. We examined the relevance of rs3135388 in childhood ALL risk along with two other HLA-DRA SNPs in two case-control groups: 114 cases and 388 controls from South Wales (UK) and 100 Mexican Mestizo cases and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…At least two studies have reported such an association; one was conducted in a Chinese population comprising 162 childhood ALL cases and 1,000 controls (15), whereas the other was conducted in a UK population, investigated the effects by gender and observed an association only in females, which is consistent with a female-specific effect of the allele DRB1*15:01, also observed in multiple sclerosis (16).…”
Section: Discussionmentioning
confidence: 58%
“…At least two studies have reported such an association; one was conducted in a Chinese population comprising 162 childhood ALL cases and 1,000 controls (15), whereas the other was conducted in a UK population, investigated the effects by gender and observed an association only in females, which is consistent with a female-specific effect of the allele DRB1*15:01, also observed in multiple sclerosis (16).…”
Section: Discussionmentioning
confidence: 58%
“…Potential interactions between HLA alleles and sex have been reported for several autoimmune disorders and human malignancies (Davis and Dorak 2010; Dorak et al 1999; Morrison et al 2010). For HLA - A variants alone, evidence of sex-specific effect further points to a short sequence motif corresponding to polymorphic amino acid residues 161, 163, and 165 of the HLA-A protein product (Song et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In other words, only girls born to mothers with multiple sclerosis may have an increased susceptibility to childhood acute lymphoblastic leukemia. 15 It is thought that EBV infection might contribute to development of breast cancer. Serum levels of EBV viral capsid antigen IgA and nuclear antigen-1 (EBNA-1) IgA are associated with the polymorphisms of IFNG (rs2069705) and IL10 (rs1800871) genes with breast cancer susceptibility in the Asian population.…”
Section: Association With Human Diseasesmentioning
confidence: 99%